Civil Society, Law and New Normal Covid -19 - Toet Hendratno, Prof. Dr.Edie (International Journal of Scientific Research and Management (IJSRM), 2021)
The Covid-19 pandemic has brought countries in the world and Indonesia is no exception entering a new phase of life. The purpose of this study is to find various policy packages by the Government and individual countries to protect their citizens in relation to various laws and regulations to overcome the Covid-19 pandemic. This type of research uses normative legal research, and the research methodology used is Foucault's theory of power relations, that is, understanding will be built to find a synthesis in this study. The results of research investigations are related to various policy packages issued by various countries and also by the Indonesian Government to protect their citizens to overcome the Covid-19 pandemic including the various effects of its dominance through large-scale social restrictions and new normal life Covid-19. However, it turns out that this provision is not effective in Indonesia because people tend to ignore it. The solution offered is that the community as a civil society must be able to manage issues in the face of inadequate public compliance with various laws and regulations that govern the handling of the Covid-19 pandemic. Therefore, Civil society in Indonesia must be encouraged to change the basis of thought so that it has the same spatial frequency as the Government